Sentra Penegakan Hukum Terpadu dalam Konsep Sistem Peradilan Pidana Pemilu - Handoko Alfiantoro (Badan Pengawas Pemilihan Umum, 2018)
The Center of Integrated Law Enforcement which is known as the “Sentra Gakkumdu” is a concrete manifestation of escort and supervision of the implementation of the General Election. The handling of alleged election crime violations has different work procedures, procedural law, and time limits, so that a one-stop handling pattern is established through Sentra Gakkumdu, which consists of elements of the Election Supervisory Body (Bawaslu), the Indonesian National Police and the Indonesian Attorney’s Office. Based on the different handling patterns in the Gakkumdu Center, it should be included in a stronger legal basis through special legislation regarding the Election Criminal Justice System, which regulates formal law and material law, and regulates the expansion of the Integrated Criminal Justice System consists of components of Sentra Gakkumdu, components of the Judiciary Institution, and components of the Penal Institution. This aims to accelerate the interconnection between individuals and institutions in the handling of alleged election crime violations in a more comprehensive manner. This article is prepared using normative juridical research methods through the Statute Approach, Comparative Approach,and Conceptual Approach, which aims to critically examine the work patterns of the Sentra Gakkumdu as a way to the Concept of the Election Criminal Justice System.